Relationship among some coordinative and dynamic strength capabilities and constructive and conceptual thinking among preschool-age children - Malambo, Chipo; Klepačová, Adéla; Brodská, Kateřina; Clark, Cain Craig Truman; Musálek, Martin (Frontiers in Psychology, 2024)
Background: Existing research underscores the positive influence of consistent physical activity, fitness, and motor coordination on school-aged children's cognitive and academic performance. However, a gap exists in fully understanding this relationship among preschoolers, a critical age group where the development of cognitive functions is significant. The study aims to expand upon existing evidence that connects motor and cognitive development by examining the correlation between specific motor coordination and physical fitness skills and the development of constructive and conceptual thinking in preschool-aged children. Methods: Data from Fifty-six children aged 4 to 5y (mean age 4.5 ± 0.36y), comprising 30 girls and 26 boys, participated in this study. We assessed muscular strength (via standing long jump, wall toss test, flexibility), agility (4x5m shuttle), cardiorespiratory fitness (20m pacer test), and motor coordination (lateral jumping, platform shifting). Cognitive abilities were measured using the IDS-P. Results: Linear regression models showed that significant predictors of constructive thinking scores were observed solely for flexibility (p = 0.02) and shifting platforms (p = 0.01). Notably, flexibility exhibited a negative relationship (β = -1.68). In the context of conceptual thinking, significant predictors (p < 0.05) included standing long jump (p = 0.01), jumping laterally (p = 0.005), shifting platforms (p = 0.001), throwing right (p = 0.02), and throwing left (p = 0.02) with jumping laterally and throwing using left hand showing negative associations. Conclusion: This study demonstrates a link between some tests of motor coordination, physical fitness skills, and constructive/conceptual thinking, recognising the need to explore these complex relationships further. Additionally, preschool curricula should include exercise units emphasising motor coordination, focusing on timing, strength, and speed in upper and lower body components.